Outlines of the ecology of England and Wales with an introductory compendium of the general principles of that science, and comparative views of the structure of foreign countries - Conybeare, William Daniel, 1787-1857 (William Phillips, 1822)
This title looks at the ecology of England and Wales and features a compendium of the general principles of that science, and comparative views of the structure of foreign countries.